Measuring Market Integration: Foreign Exchange Arbitrage and the Gold Standard, 1879–1913 - Canjels, Eugene; Prakash-Canjels, Gauri; Taylor, Alan M. (The Review of Economics and Statistics, 2004)
A major question in the literature on the classical gold standard concerns the efficiency of international arbitrage. Authors have examined efficiency by looking at the spread of the gold points, gold point violations, the flow of gold, or by tests of various asset market criteria, including speculative efficiency and interest arbitrage. These studies have suffered from many limitations, both methodological and empirical. We offer a new methodology for measuring market integration based on nonlinear theoretical models and threshold autoregressions. We also compile a new, highfrequency series of continuous daily data from 1879 to 1913. We can derive reasonable econometric estimates of the implied gold points and price dynamics. The changes in these measures over time provide an insight into the evolution of market integration.